Educator’s Understanding of Intellectual Social Emotional Skills as Strengthening Educator’s Character - Murtadho, Fathiaty; Boeriswati, Endry; Supriyana, Asep; Eriyani, Reni Nur; Parai, Hestiyani; Purwanto, Anim; Basri, La Ode Muhammad Idrus Hamid; Anisah, Lina (IJLECR (International Journal of Language Education and Cultural Review), 2024)
This research aims to analyse teachers’ understanding of Social Emotional Learning (SEL) as an effort to strengthen the character of educators. The research focus includes teachers’ understanding of: (1) the impact of implementing self-awareness, self-management, social awareness, relationship skills, and responsible decision-making in learning on teaching quality; (2) Integration of intellectual and SEL skills into critical thinking skills, creativity, collaboration, and computational logic for decision making in the learning process at class; and (3) teachers’ needs in developing the integration of intellectual and SEL skills in learning. The research method uses a phenomenological approach with data collected through surveys, in-depth interviews and observations of teachers in five provinces in Indonesia. The results show that 94% of teachers understand the importance of SEL in creating positive and inclusive learning, but only 53% are able to implement it effectively. As many as 78% of teachers succeeded in creating a conducive classroom atmosphere, while only 64% were able to understand students’ perspectives, and 45% showed sensitivity to students’ individual differences. These findings indicate that limited professional training, curriculum pressure, and high workload are the main obstacles. This research emphasizes the importance of integrating social-emotional and intellectual skills in learning to support the adaptive character of educators. Recommendations include ongoing training, policy support for resource provision, and regular reflection on teaching practice to improve teacher competency in implementing SEL.